USE OF DIFFERENT YEAST STRAIN APPROACHES IN BEER PRODUCTION: AN OVERVIEW - Azevedo, R. R.M.; Santos, C. R.B.; Sampaio, B. S.; Santos, F. S.; Simões, M. M.M.; Del Bianchi, V. L. [UNESP]; Santos, Diego Tresinari dos; Carvalho, Giovani Brandão Mafra de (My University, 2021)
In search of innovations, there are several techniques studied and tested, currently, regarding the different approaches to the use of yeasts in the beer production process. There are several ways of maintenance and different genera of yeasts, however, the lyophilization methodology and the genus Saccharomyces always stand out both in number of studies and in industrial applications. Thus, the addition of cryoprotectants in yeasts to perform lyophilization has been showing many positive results, increasing the viability and storage time of these yeasts. Despite the hegemony of the Saccharomyces genus, the discoveries of innumerable strains of wild yeasts and the use of starter or unconventional cultures have opened up a range of possibilities in the search for different aromas and flavors in beers and fermentative discoveries, such as the patented Pichia Kluyv yeast as promising in the production of low alcohol beers. In this chapter, some of these methodologies applied in the search for ways to maintain or improve the viability of yeasts during the fermentation process will be discussed and will bring sensory and technological novelties to an industry that is constantly evolving, such as the food industry.